2002
DOI: 10.1002/gcc.10042
|View full text |Cite
|
Sign up to set email alerts
|

21q22 balanced chromosome aberrations in therapy‐related hematopoietic disorders: Report from an International Workshop†

Abstract: The International Workshop on the relationship between prior therapy and balanced chromosome aberrations in therapy-related myelodysplastic syndromes (t-MDS) and therapy-related acute leukemia (t-AL) identified 79 of 511 (15.5%) patients with balanced 21q22 translocations. Patients were treated for their primary disease, including solid tumors (56%), hematologic malignancy (43%), and juvenile rheumatoid arthritis (single case), by radiation therapy (5 patients), chemotherapy (36 patients), or combined-modality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 97 publications
7
71
1
Order By: Relevance
“…Interestingly, 7qÀ/ À7 was in the International Workshop Study of t-MDS and t-AML the most common secondary cytogenetic abnormality in patients with balanced translocations to chromosome band 21q22. 33 We have observed defects of chromosme 7 in five of nine patients with translocations to 21q22 and rearranged AML1. Thus, abnormalities of AML1 of two types, point mutations as observed in pathway I, and chimeric gene fusions as observed in pathway IV, are both associated with defects of chromosome arm 7q.…”
Section: Pathway IVmentioning
confidence: 73%
See 1 more Smart Citation
“…Interestingly, 7qÀ/ À7 was in the International Workshop Study of t-MDS and t-AML the most common secondary cytogenetic abnormality in patients with balanced translocations to chromosome band 21q22. 33 We have observed defects of chromosme 7 in five of nine patients with translocations to 21q22 and rearranged AML1. Thus, abnormalities of AML1 of two types, point mutations as observed in pathway I, and chimeric gene fusions as observed in pathway IV, are both associated with defects of chromosome arm 7q.…”
Section: Pathway IVmentioning
confidence: 73%
“…Also these abnormalities have been associated with previous therapy with topoisomerase II inhibitors, most often anthracyclines. [31][32][33] Seven of our 10 patients in this pathway had received topoisomerase II inhibitors. Whereas patients with t(3;21)(q26;q22) and rearrangement between the EVI1 and AML1 genes often present as t-MDS, most other patients belonging to pathway IV present as overt t-AML ( Figure 1).…”
Section: Pathway IVmentioning
confidence: 99%
“…1): 273a; abstract) cannot explain the worse outcome, as a study on 44 cases with t-AML and t (8;21) showed no difference in outcome between cases with and without additional karyotype aberrations. 44 In 48 cases with t-AML and inv(16) and 44 t-AML with t(15;17) also, no prognostic impact of secondary chromosome aberrations was observed. 45 t-AMLs are often excluded from therapeutic trials and therefore are treated on a more individual basis that might be less intensive, although in this study treatment within a clinical trial did not influence outcome in patients with favorable karyotype.…”
Section: Prognostic Impact Of Karyotype and T-aml C Schoch Et Almentioning
confidence: 97%
“…The median OS of t-AML cases with t(8;21) as the sole abnormality and for cases with t(8;21) and additional chromosome aberrations was comparable (17.0 and 30.9 months, NS) as reported from the International Workshop on balanced translocations in t-AML. 44 The respective data from de novo clinical trials show a median OS of 61 months 31 and an overall survival rate at 5 years of 52 and 59%, respectively. 31,32 Overall, t-AMLs with favorable cytogenetics show an inferior outcome compared to their de novo counterparts.…”
Section: Prognostic Impact Of Karyotype and T-aml C Schoch Et Almentioning
confidence: 99%
“…29 Their median survival was 14 months, and 18% were alive after 5 years. Patients with t(8;21) had a more favorable outcome than those with other 21q22 rearrangements (P = .014).…”
Section: Recommendations For Treatment Of T-amlmentioning
confidence: 98%